AESTHETIC AND FUNCTIONAL PARAMETERS OF THE MENTOLABIAL GROOVE IN THE OROFACIAL HARMONIZATION OF THE MENTAL REGION: CASE REPORT - Lisboa Macedo, Kemerson; Cristina Maurício Milagre Diniz, Helen (Health and Society, 2022)
There have been many techniques and approaches in the treatment of orofacial harmonization of the lower third of the face, however, in many cases, the mentolabial sulcus area does not receive due attention in this process. Therefore, the objective of this study is to carry out a case report that analyzes the aesthetic and functional parameters of the mentolabial sulcus in the orofacial harmonization of the chin region for a more complete and efficient facial rejuvenation. In order to reach the proposed objective, a clinical case report was made with a female patient, with no history of alcoholism and smoking, in good health. The patient underwent anamnesis, clinical examination and proposed, for her case, the use of three syringes of hyaluronic acid of a known brand, in the middle and lower thirds of the face. At the end of the treatment, the patient presented greater luminosity in the filled areas, a good reduction of facial creases and an expressive rejuvenation of the chin region, where a decrease in shadows and an increase in the mentolabial angle can be observed. From that case, a detailed study of the aesthetic and functional parameters of the mentolabial sulcus in orofacial harmonization was carried out, from which important conclusions can be drawn.